Two-dimensional coding phase gradient metasurface for RCS reduction. (10th August 2018) - Feng, Maochang; Li, Yongfeng; Zheng, Qiqi; Zhang, Jieqiu; Han, Yajuan; Wang, Jiafu; Chen, Hongya; Sai, Sui; Ma, Hua; Qu, Shaobo
Abstract: A two-dimensional (2D) coding phase gradient metasurface (CPGM) is proposed for radar cross section (RCS) reduction in this work. The 2D phase gradient super cell is employed to serve as the coding element. The primary pattern of the coding element will be modulated by the designed 2D phase gradient. Thus, a more flexible method of scattering manipulation will be achieved by both the 2D phase gradient and coding sequences. The specific scattering patterns of the 2D CPGM under the modulation of phase gradient and coding sequence were analyzed. A controllable backward diffusion scattering coding phase gradient metasurface was realized based on Pancharatnam–Berry phase by modulating both the phase gradient and coding sequence. Both simulated and measured results demonstrate its excellent performance on RCS reduction.